2010
DOI: 10.1007/s11604-009-0396-2
|View full text |Cite
|
Sign up to set email alerts
|

Experimental verification of age-dependent cisplatin-induced nephrotoxicity in rats using dynamic contrast-enhanced computed tomography

Abstract: This study demonstrated the existence of age-dependent difference in cisplatin-induced nephrotoxicity in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Some authors observed that normal and cancer cells were sensitive to the EMF [Di Loreto et al, 2009; Garip and Akan, 2010] and that the application of 1–10 mT of ELF‐EMF was toxic and could induce genetic damage to these cells [Harris et al, 2002; Wolf et al, 2005; Villarini et al, 2006]. Cisplatin also induces oxidative stress in the hepatic tissue of rats [Pratibha et al, 2006], human renal cells [Tachibana et al, 2010], human laryngeal carcinoma cells [Paduch et al, 2009], and other types of cells [Attia, 2010].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors observed that normal and cancer cells were sensitive to the EMF [Di Loreto et al, 2009; Garip and Akan, 2010] and that the application of 1–10 mT of ELF‐EMF was toxic and could induce genetic damage to these cells [Harris et al, 2002; Wolf et al, 2005; Villarini et al, 2006]. Cisplatin also induces oxidative stress in the hepatic tissue of rats [Pratibha et al, 2006], human renal cells [Tachibana et al, 2010], human laryngeal carcinoma cells [Paduch et al, 2009], and other types of cells [Attia, 2010].…”
Section: Discussionmentioning
confidence: 99%